DAMPAK ORGANIZATIONAL LEARNING CAPABILITY DAN ORGANIZATIONAL CULTURE TERHADAP ORGANIZATIONAL INNOVATION PADA PEGAWAI PDAM TIRTA SORUME KABUPATEN KOLAKA - Putri, Fitrah Amalia; Wonua, Almansyah Rundu; Kumalasari, Fitri (University of Riau Kepulauan, 2025)
This research was conducted at PDAM Tirta Sorume, a regional company providing clean water in Kolaka Regency, which faces issues of lacking organizational innovation. The study investigates (1) how Organizational Learning Capability (OLC) can affect Organizational Innovation (OI) among PDAM Tirta Sorume employees and (2) how Organizational Culture (OC) can impact Organizational Innovation among PDAM Tirta Sorume employees. This research uses a quantitative method with a population and sample of 93 respondents. Instrument testing techniques include validity and reliability tests using SPSS Version 23.0. The data testing technique employs the measurement model (outer model) and structural model (inner model) through SMARTPLS Version 3.0. Based on the results, it was found that there is a positive and significant effect between the OLC variable on OI, with an original estimate value of 0.256 and a p-value of 0.045. The analysis results also show that OC has a meaningful positive impact on OI, as evidenced by a t-statistic value of 5.178 and a p-value of 0.000, indicating a statistically strong relationship between the two variables